APLIKASI KURIKULUM MERDEKA BELAJAR DI SMP NEGERI 24 MEDAN SEBAGAI PENANAMAN BUDAYA KEWARGANEGARAAN - Jessica Evi Margaretha Simanjuntak; Julia Ivana (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2022)
The purpose of writing this article is to see how the independent learning curriculum is implemented at SMP Negeri 24 Medan. The data collection is done by observation and literature study. Observations made by the author were to observe the teaching and learning conditions at SMP Negeri 24 Medan related to the implementation of the Merdeka curriculum and the subjects in this study were grade 1 teachers at SMP Negeri 24 Medan. The independent curriculum is a form of innovation as well as an effort to prepare Indonesian education in the face of developments in socialization and modernization. This is because so that the younger generation is able to compete in the digitalization era and look for competent human resources so that the Merdeka Learning curriculum is proclaimed as a curriculum based on the concept of 21st century education and IT-based. The orientation of the Freedom to Learn curriculum is how learning is innovated with interesting things and certainly not spared from technological elements. So that in carrying out learning activities an approach that accommodates the characteristics of 21st century learning is needed. In elementary learning, including at SMP Negeri 24 Medan, where the compulsory subject is mathematics, where the subject is a subject that is categorized as a difficult subject for students. students also include science subjects which contain exact and quantitative elements.